Organizational Elements that Shape Construction Employees’ Approach and Behavior Towards OSH - Vimlesh Prabhu Desai; Lysette D’souza; Anil Singh; Vikram Bhadauria (Journal of Engineering, Project, and Production Management)
The construction industry has one of the highest known rates of occupational incidents. Construction organizations are increasingly recognizing the significance of occupational safety and health (OSH) problems as a prominent area of concern. Though numerous studies have shown that employees’ behavior and approach towards OSH are impacted by Environmental (such as governmental regulations), Personal and Organizational factors, there is a lack of consensus on the organizational elements. Hence, the primary objective of this study is to ascertain the organizational elements that influence employees’ adherence to OSH and suggest improvement needs, if any. To achieve the objective, the study adopted a qualitative research approach and conducted semi-structured interviews with fifteen highly experienced professionals in the construction industry. Using manual thematic analysis, the interview transcripts were analyzed to identify and extract major themes based on commonalities. Six themes were recognized: Empowerment, communication, knowledge management and learning and development, leadership and top management commitment, internal systems and processes, and work culture and spirituality. The findings of this study will assist the industry in developing a framework of effective solutions for OSH management. These themes can form the basis of a good approach to an integrated OSH strategy.